Lie. skélti, skẽlia ir skelė́ti, skẽli – panašumas ar giminystė? - Kaukienė, Audronė; Jakulis, Erdvilas (Baltistica, 2007)
LITH. skélti, skẽlia ‘TO SPLIT’ AND skelė́ti, skẽli ‘TO OWE’ – SIMILARITY OR RELATIONSHIP? The article discusses the question of the connection between Lith. skélti ‘to split, etc.’ and Lith. skelė́ti ‘to owe’. Many linguists thought that there was no relation between them or it was dubious. They used to relate Lith. skelė́ti with kal̃tas ‘guilty’. Although the latter relation can’t be direct, it can be seen only in Indo-European parent language level. After the analysis of related words in Lithuanian, Latvian, Old Prussian and other Indo-European languages and after typological analysis the authors of the article make conclusion that there is not any morphological or semantic obstacles to relate verbs Lith. skélti, skẽlia, skė́lė tr. ‘to split, etc.’ and skelė́ti, skẽli (-a, -ia) intr. ‘to owe’. These verbs could originate from verbal paradigm (*skilti, *skela, *skilė), which had split into several of verbs: a) Lith. skélti, skẽlia, skė́lė tr. ‘to split, etc.’ (Latv. šķel̑t, šķeļu, šķēļu „to split, to cleave, to chop, to strike‘); b) Lith. skìlti, ‑ia, skýlė tr. ‘to break, to strike for making fire’ (la. šķil̃t, -ļu, šķĩļu ‘idem’); c) Lith. skìlti, skýla intr. 1. ‘to split, to fracture’ 2. ‘to get into debt’; d) Lith. skelė́ti, skẽli (-a, -ia) intr. ‘to owe’. The original meaning ‘tr., intr. to split, to fracture’ of the root *skel- is better preserved in Eastern Baltic languages (Lith. tr. skélti, skẽlia, skė́lė, Latv. tr. šķel̑t, šķeļu, šķēļu : Lith. intr. skìlti, skýla). This meaning can be also reconstructed from Old Prussian derivatives scolwo „chip, shingle“, scalus „chin“. The embranchment of verbal root *skilti, *skela, *skilė continued in Lithuanian even after the split of eastern Baltic languages. Therefore the more verbs of this root have been formed in Lithuanian than in Latvian. On the other hand the meaning of status and variety of present forms may also indicate that the verb skelė́ti ‘to owe’ could be a derivative, but not the result of the word-transformation. There is not any structural equivalent of the verb skelė́ti in Latvian. The verb skelė́ti has been formed in Western Lithuania. It is corresponded by the verbs of various structures in Old Prussian (*skel-ē-twei, *skal-ī-twei, *pa-skāl-ī-twei). As the result of influence of German language the new meaning ‘to ought, to suppose to’ was added in Old Prussian. The meanings ‘to owe’, ‘debt’ should be considered as formed from the older one. The possible ways of this formation are these: 1) ‘to split’ → ‘to mark the debt by splitting, cutting (the debt stick)’ → ‘to owe’; 2) ‘to split’ → ‘to give by splitting off / to have what is splitted off’ → ‘to owe’; 3) ‘to split’ → ‘lack, crack, split, gap’ → ‘debt’. These meanings has been formed in Lithuanian ir Old Prussian. The most popular derivatives in Lithuanian is the noun skolà ‘debt’ (which can be derived directly from the verb skélti, or from the verb. skelė́ti) and its derivative adj. skolìngas ‘owing’; the dialects also use adj. skal̃nas ‘idem’. The formation of several lexemes with different semantics from the root praes. *skel-, praet. *skol- / *skl̥- is also characteristic to Germanic languages (OGH skiljan, OISL skilja ‘to separate. to divide, to decide’ / go. skal, skulun, skulda ‘to ought, to owe’). The meanings ‘debt’ and ‘duty’ (: ‘to ought’) are tightly connected. However the meaning ‘guilt’ appears only in German languages and in the languages that have definite contacts with Germans. Because of the influence of Germans this meaning also slightly touches the Baltic languages. Nevertheless it should be considered as a new one. So, the attempts to cognate the verb skelė́ti ‘to owe’ with the adj. kal̃tas ‘guilty’ have neither structural nor semantic reason.